PERANCANGAN WEBSITE ANGKASA PURA-NOTEBOOK: SISTEM PENCATATAN LOG HARIAN GUNA MENDUKUNG OPERASIONAL TERMINAL DI BANDARA INTERNASIONAL I GUSTI NGURAH RAI - Putu Ananda Darma Wiguna; Luh Gede Astuti; I Gusti Ngurah Anom Cahyadi Putra (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
In a case study at I Gusti Ngurah Rai International Airport, recording daily logs by the operational team still faces challenges in terms of efficiency, consistency, and speed of information distribution. In response to these needs, a centralized web-based system called Angkasa Pura-Notebook was developed that is designed to record, monitor, and present information on operational activities and facility conditions in real-time. The development process involves analyzing user needs, designing interfaces, building the system using Laravel and Tailwind CSS, and evaluating through training and direct trials in the work environment. The implementation results show that the system has successfully improved coordination between shifts, made it easier to track facility conditions, and accelerated responses to operational constraints. By minimizing miscommunication and supporting structured digital record keeping, Angkasa Pura-Notebook is an effective solution to strengthen overall airport operational performance.